ESTUDIOS HELMINTOLOGICOS DE LA CUENCA DEL RIO PAPALOAPAN III STRIGEIDOS DE LOS LAGARTOS DE MEXICO - CABALLERO Y C, EDUARDO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1948)
Griebel's discovery of a new fruit acid (hibiscic acid) in Hibiscus sabdariffa was confirmed The prepn of a phenacyl ester of this acid showed that the substance isolated from the Mexican drug jamaica is identical with that isolated by Griebel from the
AN ESC NAC CIENC BIOL
Keywords: ESTUDIOS HELMINTOLOGICOS, CUENCA DEL RIO PAPALOAPAN III, STRIGEIDOS, LAGARTOS, MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL